Beyond immigration: Moving from Western to Global Indexes of Migration Policy. Issue 3 (11th June 2021) - Solano, Giacomo; Huddleston, Thomas
Abstract: Over the last twenty years, researchers have undertaken systematic comparison of migration policy by creating sets of policy indicators/indexes at the national level. These indicators are designed to analyse the differences and trends in migration policy and then be used by the research community to assess the determinants and effects of policy. This article aims to assess the comprehensiveness of current migration policy indicators by analysing their thematic, geographical and temporal coverage as a way of understanding how migration policy has been conceptualised and measured in quantitative migration research. Our analysis of the 67 existing indexes shows that they disproportionally focus on immigration policy, mainly admission and citizenship, in OECD and particularly Western European countries, with limited opportunities for longitudinal analysis of policy change. These findings reveal that migration policy has been largely conceptualised in indexes as a contemporary phenomenon, concerning mainly Western countries that have become major destination countries. Abstract : While thematic, geographical and temporal gaps persist, the situation has recently improved in terms of the development of the field of migration policy indexes.